Doctorate nursing degree in Spain - Mª José López-Montesinos; Loreto Maciá-Soler (Universidade de São Paulo, 2015)
Analytical and descriptive study of the process of change being experienced in the Spanish university system over the last decade (2005-2014).OBJECTIVE: To describe the structural changes occurring in Nursing Education in Spain, reaching access to doctoral studies from the European Convergence Process and the subsequent legislative development.METHODOLOGY: Bibliographical review of royal decrees and reference literature on the subject of study and descriptive analysis of the situation.RESULTS: Carries various changes suffered in the curricula of nursing education in the last decade, the legislation of the European Higher Education sets the guidelines for current studies of Masters and Doctorates.CONCLUSIONS: The implementation of the Master and Doctorate stages after a basic degree, which is now possible with the new legislation. A formal beginning made of scientific nursing in order to generate their own lines of research led by Doctors of nursing who can integrate in research groups under the same condition as other researcher, yet now, from the nursing discipline itself.